Structured Microfinance in China - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2007)
In this paper we discuss the potential for commercial microfinance in China. Particular emphasis is put on securitization of microloans and on structured microfinance in a China context. Three particular factors that we believe could support a strong growth in Chinese structured microfinance are (i) the lack of currency risk, (ii) the scale advantages and (iii) the massive potential interest from traditional, domestic as well as international, financial firms. On the policy side, structured microfinance could be an important tool for fighting unemployment in China. It could also be used to circumvent corruption or government bureaucracy in the microlending process.
Keywords: G10; G21; O16; R51; 330; commercial microfinance; structured finance; securitization; China